2018
DOI: 10.28991/cej-0309100
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Harmony Search Optimization to Predict Local Scour Depth around Complex Bridge Piers

Abstract: One of the main causes of bridge collapse may be flood flow scour near piers. Several experimental and local field investigations were carried out to study scour depth. However, existing empirical equations do not commonly provide accurate scour prediction due to the complexity of the scour process. Physical and economic considerations often lead to bridge foundation constructs which included a pier column based on a pile cap supported by an array of piles. Piers with this configuration are referred to as comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…A comparison of experimental and regression model results (a) Equation 4, and (b) Equation 5In Figure 6(a), the linear regression fit was made between the experimental values and the calculated values presented for the dimensionless parameter (Equation (4)), so that the correlation coefficient R 2 and the regression line slope α equaled 0.97 and 1.01, respectively, which suggested a very good performance of the relationship. Moreover, in Figure 6(b), the same comparison was made for Equation (5), so that the correlation coefficient R 2 and regression line slope α equaled 0.93 and 0.98, respectively, which also showed that the relationship had a good performance.…”
Section: Equipment and Testing Methodsmentioning
confidence: 80%
See 1 more Smart Citation
“…A comparison of experimental and regression model results (a) Equation 4, and (b) Equation 5In Figure 6(a), the linear regression fit was made between the experimental values and the calculated values presented for the dimensionless parameter (Equation (4)), so that the correlation coefficient R 2 and the regression line slope α equaled 0.97 and 1.01, respectively, which suggested a very good performance of the relationship. Moreover, in Figure 6(b), the same comparison was made for Equation (5), so that the correlation coefficient R 2 and regression line slope α equaled 0.93 and 0.98, respectively, which also showed that the relationship had a good performance.…”
Section: Equipment and Testing Methodsmentioning
confidence: 80%
“…This structure is an economical alternative to other conventional dissipators such as stilling basins, etc. [4,5]. So far several studies have been carried out to address scouring downstream of flip bucket jets by Bormann and Julien [6]; Jafari and Khiavi [7], Mason and Arumugan [8], Amanian and Urroz [9], Stein et al [10], Afify and Urroz [11] and Cordier et al [12].…”
Section: Introductionmentioning
confidence: 99%
“…ant colony [77], water flow, and an ensemble of musicians [78]. Some illustrations of the metaheuristic techniques in addition to genetic algorithm (GA) [79,80], harmony search (HS) [81], firefly algorithm (FA) [82], Tabu search (TS) [83], artificial bee colony (ABC) [84], teaching-learning-based optimization (TLBO) [85], particle swarm optimization (PSO) [86], bat algorithm (BA) [87], cuckoo search (CS) [79], and many others. To characterize metaheuristic algorithms, taxonomies founded on specific features of algorithms are created [88], Nature-inspired vs. non-nature-provoked objective functions, population-based vs. trajectory-based objective functions, and dynamic vs. static objective functions are only a few examples.…”
Section: Optimization Techniques and Methodsmentioning
confidence: 99%
“…Because of the complicated process of scour around bridge piers, the local scour depth at complex pier (LSCP (is a complicated phenomenon and hence its accurate predictions are a critical issue for the design of bridge foundations. In other words, overestimation of LSCP may lead to extra construction costs and even bridge failure around their foundations [3].…”
Section: Introductionmentioning
confidence: 99%